Synaptobrevin-2 disease variants reveal spatial constraints within the presynaptic active zone - Natalie J. Guzikowski; Elena D. Bagatelas; Ok-Ho Shin; Yousuf A. Khan; Luis Esquivies; Baris Alten; Axel T. Brunger; Ege T. Kavalali (Proceedings of the National Academy of Sciences, 2025)
Soluble N-ethylmaleimide-sensitive factor attachment protein receptor (SNARE) proteins drive synaptic transmission in a temporally and spatially precise manner. Recent studies have identified several disease-causing SNARE variants that give rise to developmental and epileptic encephalopathies, defined as SNAREopathies. Here, we investigated nine synaptobrevin-2 (VAMP2) disease-causing variants and uncovered their specific SNARE complex affinity, stability, and conformational deficits that drive dysregulated neurotransmission. The neurotransmission deficits we observed parallel the symptomatic heterogeneity of the patients, with some variants displaying a disproportionate augmentation of spontaneous neurotransmitter release. When we examined the spatial organization of this excessive spontaneous release at nanoscale, we found that SNARE complexes composed of these variants formed exclusively outside of RIM scaffolding, revealing a preserved exclusion zone sparing evoked release from pathophysiology. Taken together with the phenotypes of previously reported disease-causing SNARE variants, these findings reveal shared patterns of aberrant neurotransmission across different SNAREs, highlighting the necessity for a functional classification of SNAREopathies to develop therapeutic interventions. The use of clinically relevant genetic manipulations to challenge the synapse provides mechanistic insight into rare diseases while simultaneously revealing fundamental aspects of synaptic physiology.